INTERPRETATION AND PREDICTION OF TRIPLE-LAYER MODEL CAPACITANCES AND THE STRUCTURE OF THE OXIDE-ELECTROLYTE-WATER INTERFACE - Sverjensky D.A. (My University, 2001)
The interpretation of mineral-water interactions in processes such as surface-charge development, adsorption of aqueous ions onto surfaces, and the kinetics of dissolution at the scale of the oxide-electrolyte-water interface has been greatly facilitated by models of the electric double layer. In models that explicitly account for adsorption of the electrolyte ions, a critical parameter is the integral electric capacitance that expresses the charge at the surface relative to the drop in electric potential at some distance away from the surface where the electrolyte ions adsorb. Despite the widespread application of such surface complexation models, much uncertainty surrounds the choice of values of the integral capacitance because it appears to depend on the specific oxide and type of electrolyte, yet it cannot be directly measured.In the present study, it is shown that triple-layer model capacitances (C1), obtained in a consistent manner from regression of surface-charge data referring to a wide range of ionic strengths, electrolyte types, and mineral surfaces, fall into two groups: on rutile, anatase, and magnetite, values of C1 increase with decreasing crystallographic radius of the electrolyte cation from Cs+ to Li+; on quartz, amorphous silica, goethite, hematite, and alumina, values of C1 increase with decreasing hydrated electrolyte cation radius from Li+ to Cs+. The triple-layer model capacitances on both groups of solids can be described by a model of the mineral-water interface with physically reasonable parameters consistent with X-ray standing-wave studies of the rutile-water interface (Fenter et al., 2000). The model specifies a layer of chemisorbed water molecules at the surface and a layer of adsorbed electrolyte cations. On rutile, anatase, and magnetite, the layer of chemisorbed water molecules is interpenetrated by the layer of electrolyte cations that adsorb close to the surface as dehydrated, inner-sphere complexes. On quartz, amorphous silica, goethite, hematite, and alumina, the layer of chemisorbed water molecules varies from 0.0 to as much as 6.0 Α and the electrolyte cations form hydrated, outer-sphere complexes. The model capacitances are consistent with interfacial dielectric constants ranging from 20 to 62. Triple-layer model capacitances can now be predicted for oxides in either alkali or alkaline earth electrolyte solutions that have not been studied experimentally. In addition, predictions can be made of the structure of the oxide-electrolyte-water interface for many oxides and electrolytes.